2013
DOI: 10.7567/jjap.52.07ha01
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonication: An Efficient Agitation for Accelerating the Supersaturation-Limited Amyloid Fibrillation of Proteins

Abstract: Amyloid fibrils are self-assemblies of proteins with an ordered cross-β architecture. Because they are associated with serious disorders, understanding their structure and mechanism of fibrillation is important. Irradiation with ultrasonication leads to fragmentation of amyloid fibrils, useful for seeding experiments. Recently, ultrasonication has been found to trigger the spontaneous formation of fibrils in solutions of monomeric amyloidogenic proteins. The results indicate that amyloid fibrillation is simila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
38
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 66 publications
(137 reference statements)
1
38
0
Order By: Relevance
“…Previous studies showed that crystal-like ordered states including amyloid fibrils do not form rapidly because of the high free energy of nucleation (19,23), which leads to supersaturation in which, in the absence of agitations to induce nucleation, the solutes may retain apparent solubility indefinitely under the conditions of metastability. On the other hand, when solvent-excluded conformations are glassy amorphous aggregates, which is common for larger denatured proteins, aggregation has been shown to occur rapidly without a lag phase.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies showed that crystal-like ordered states including amyloid fibrils do not form rapidly because of the high free energy of nucleation (19,23), which leads to supersaturation in which, in the absence of agitations to induce nucleation, the solutes may retain apparent solubility indefinitely under the conditions of metastability. On the other hand, when solvent-excluded conformations are glassy amorphous aggregates, which is common for larger denatured proteins, aggregation has been shown to occur rapidly without a lag phase.…”
Section: Discussionmentioning
confidence: 99%
“…The same effects may be induced by other types of agitations such as stirring. One possible mechanism is the condensation of amyloidogenic proteins at the water/air interface produced by ultrasonication-induced cavitation or stirring (19,23). Local increases in the protein concentration at the water/air interface have been shown to lead to glassy aggregates, in which a template-competent conformation may emerge.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study, ultrasonic treatment, one of the most powerful methods for accelerating spontaneous fibrillation in vitro, was used to efficiently investigate the amyloid fibrillation of keratoepithelin-derived peptides (27)(28)(29)(30). We used the wildtype R-peptide and disease-associated C-type and H-type peptides.…”
mentioning
confidence: 99%